2020
DOI: 10.1093/ibd/izaa002
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism After Hospital Discharge in Patients With Inflammatory Bowel Disease: A Population-based Study

Abstract: Background Inflammatory bowel disease (IBD) is associated with a high risk of venous thromboembolism (VTE) during hospitalization. It is unclear if this association persists after discharge. We aimed to assess the incidence of postdischarge VTE in IBD patients and to determine if IBD is associated with increased VTE risk. Methods We performed a population-based cohort study between 2002 and 2016 using Ontario health administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…As the burden of TE events remains a substantial public health concern, it is important to continue to examine the strength of this potential safety signal in real-world data. This is particularly true for JAKinibs since they are indicated for, and commonly prescribed to, patients experiencing a broad range of IMDs, such as rheumatoid and psoriatic arthritis as well as UC, all of which already have a high background risk for TEs [18][19][20][21].…”
Section: Data Cleaning Proceduresmentioning
confidence: 99%
“…As the burden of TE events remains a substantial public health concern, it is important to continue to examine the strength of this potential safety signal in real-world data. This is particularly true for JAKinibs since they are indicated for, and commonly prescribed to, patients experiencing a broad range of IMDs, such as rheumatoid and psoriatic arthritis as well as UC, all of which already have a high background risk for TEs [18][19][20][21].…”
Section: Data Cleaning Proceduresmentioning
confidence: 99%
“…However, the lowest incidence was seen in patients with CD (1.2%). Similarly, McCurdy et al [ 93 ] reported that the cumulative incidence of VTE at 1 mo after discharge was higher in surgical patients with UC (HR: 1.68; 95%CI: 1.16–2.45) but not in surgical patients with CD. In UC patients, the risk of VTE is mostly higher in patients after colectomy[ 94 , 95 ].…”
Section: Risk Factors Of Thromboembolic Complications In Ibdmentioning
confidence: 90%
“…Finally, it is well known that surgery represents a major risk factor for VTE, particularly in patients with IBD, and thromboprophylaxis is universally performed from the day of surgery to discharge. However, as reported before, in the IBD patient population, colorectal surgery is related to an additional VTE risk, including post-discharge period[ 93 , 95 ]. Recent meta-analyses in the United States indicated that IBD patients undergoing colorectal surgery were at a higher in-hospital and post-discharge risk for postoperative VTE compared to non-IBD patients undergoing surgery for colorectal cancer[ 91 , 99 ].…”
Section: Prophylaxis Of Vte In Ibdmentioning
confidence: 90%
See 1 more Smart Citation
“…The risk of lymphoma is increased in RA and especially so in patients most severely affected by RA, namely, those who may have the greatest need for TNF blockers. In addition, the background risk of VTE is also increased in other diseases for which jakinibs are approved, such as ulcerative colitis [39] and psoriatic arthritis [36].…”
Section: Jak Thrombosismentioning
confidence: 99%